2023
DOI: 10.3390/su15032380
|View full text |Cite
|
Sign up to set email alerts
|

X-TEAM D2D Project: Designing and Validating a Concept of Operations for Door-To-Door Multimodal Transport

Abstract: The project X-TEAM D2D (extended ATM for door-to-door travel) has been funded by SESAR JU in the framework of the research activities devoted to the investigation of integration of Air Traffic Management (ATM) and aviation into a wider transport system able to support the implementation of the door-to-door (D2D) travel concept. The project defines a concept for the seamless integration of ATM and Air Transport into an intermodal network, including other available transportation means, such as surface and water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…From this wide spectrum identified for UAM applications, the project selected the applications more related to general public utility and services, and focused on these as the most promising ones in terms of overall societal impact in everyday life and in terms or biggest expected positive impact on the overall urban mobility: the goods delivery and the transport of people. The ConOps, therefore, has been detailed considering 6 Use Cases (UCs), in incremental way according to the three baseline Based on the project studies, the cargo applications are expected to be matured and routinely operated already by 2030, whereas for transport of people the 2035 time horizon can be considered the first step in experimental application, being instead the full maturity of this application expected by 2050, in compliance with the X-TEAM D2D studies [11]- [17]. The ASSURED UAM ConOps and Use Cases studies overall results are reported in [10].…”
Section: Easn-2022mentioning
confidence: 99%
See 1 more Smart Citation
“…From this wide spectrum identified for UAM applications, the project selected the applications more related to general public utility and services, and focused on these as the most promising ones in terms of overall societal impact in everyday life and in terms or biggest expected positive impact on the overall urban mobility: the goods delivery and the transport of people. The ConOps, therefore, has been detailed considering 6 Use Cases (UCs), in incremental way according to the three baseline Based on the project studies, the cargo applications are expected to be matured and routinely operated already by 2030, whereas for transport of people the 2035 time horizon can be considered the first step in experimental application, being instead the full maturity of this application expected by 2050, in compliance with the X-TEAM D2D studies [11]- [17]. The ASSURED UAM ConOps and Use Cases studies overall results are reported in [10].…”
Section: Easn-2022mentioning
confidence: 99%
“…The reference papers that described up to date the project evolution are in particular the works from [1] to [6] indicated in the references, whereas the full collection of the project reported outcomes is publicly available through the deliverables indicated in the references from [7] to [10]. It is worth noticing, finally, that the ASSURED UAM project works in close cooperation, with efficient cross-fertilization in particular with reference to the UAM integration into overall multimodal transport network related aspects, with the X-TEAM D2D (Extended ATM for Door-to-Door travel) project, as addressed in the reference papers from [11] to [17]. The main focus of this paper is on the summary description of the outcomes from the project activities that have been carried out to develop operational concepts for UAM deployment in the next decades.…”
Section: Introductionmentioning
confidence: 99%
“…To explore how passenger journeys will change with the implementation of multimodal networks throughout Europe, we transferred the concept of operations (ConOps) of such a system into a simulation platform that allows us to estimate its performance. The evaluated ConOps was the one developed by the X-TEAM D2D project [5][6][7][8]. The details of the ConOps and its background analysis can be found in [52][53][54][55][56].…”
Section: Conceptual Design Of a Multimodal Network In 2025 2035 And 2050mentioning
confidence: 99%
“…To explore how such integration and emerging transport technologies influence passengers' journeys, this work presents a study on how future multimodal transportation networks will impact passenger travel. The work is based on the concept of operations developed in the X-TEAM D2D project [5][6][7][8], where the authors were focused on modelling the concept of operations for the multimodal network.…”
Section: Introductionmentioning
confidence: 99%
“…More details about the X-TEAM D2D project overall application framework have been already provided in the previous works and so are no further addressed here, in order to be able to allocate bigger room in this paper on the description of the contents indicated in the abstract. The reference papers that described the project evolution are in particular the works from [1] to [6] indicated in the references, whereas the full collection of the project reported outcomes is publicly available through the deliverables indicated in the references from [7] to [12]. It is worth noticing, finally, that the X-TEAM D2D project worked in close cooperation with siblings running projects and, in particular with reference to the UAM related aspects, cooperated and provided relevant outcomes as well as received relevant information, with efficient cross-fertilization, with the ASSURED UAM (Acceptance, Safety and Sustainability Recommendations for Efficient Deployment of UAM) project, as addressed in the reference papers from [13] to [18].…”
Section: Introductionmentioning
confidence: 99%